Pick n Pay customer self-service mobile application - Masvingise, Rumbidzai Rashel (Midlands State University, 2017)
Technology is changing rapidly and there is need to adjust so as to improve the economy and how businesses operate in Zimbabwe. This research gives a detailed overview of the Pick n Pay Self-Service Mobile application with the main thrust of solving the problems of having long queues customers waiting to pay up goods, customers spending much than they have budgeted and increase in stationary costs during business operation, at the same time with the main of implementing new technologies in Zimbabwe that will help improve our economy through the improvement of business operations. The system will enable customers to purchase groceries through the scanning of barcodes using android smart phones and a virtual receipt being generated soon after payments of commodities. The system has a windows based application that will be used for the creation of account and product pricing by the internal users of Pick n Pay stores, and also it has a mobile application that will act as an interface between customer and the system resources. Researcher used interviews, questionnaires and observation scorecards as methodologies to acquire information that would help in system development. A windows based application was developed using CSharp programming language while the mobile application was developed using java. Major reason for carrying out the research is to curb the problems of the current system highlighted above at the same time increasing organizational sales.